Ethylene oxide (EtO) : understanding OSHA's exposure monitoring requirements : making the right decisions---how to comply with the EtO standard. (U.S. Dept. of Labor, Occupational Safety and Health Administration, 2007)
The purpose of this guidance document is to help employers understand how to monitor the quality of the air in workplaces where ethylene oxide (EtO) is processed, used, or handled. Air monitoring is an important activity that can help alert employers when unsafe levels of EtO are present in the air so that they can take steps to reduce employee exposure. EtO can be used more safely if appropriate precautions are taken and if equipment is adequately designed and maintained.